Set peluang pelaburan, polisi syarikat serta pengaruhnya terhadap nilai syarikat - Mamat, Sulaiman (2012)
This research study the relationship among investment opportunity set (IOS) with firm value, managerial ownership and firm policies in Malaysia. As a proxy of company is growth opportunities, investment opportunity set (IOS) was hypothesized to have a positive impact toward the firm value. However, the relationship is indirect in nature and need to go through the company policies such as dividend policy and capital structure policy that were determined by company is management. Population and sample of current research are the manufacturing company listed in Bursa Saham Malaysia (BSM). Duration of this study is from year 2000 until year 2004 which is 5 years after Malaysian recession crisis in years 1997 and 1998. This study found that the growth opportunities have positive relationships with firm value. However, the growth opportunities have negative relationship and significant with capital structure policy. On the other hand, growth opportunities have significant and positive relationship with dividend policy. Multiple regression analysis was done to identify the role of dividend policy and capital structure policy as mediating variables. The analysis found that dividend policy does not had impact as mediating variables toward the relationship between company growth opportunity and firm value. However, capital structure policies have effect as a mediating variable.